Comparison of Petrophysical Properties Measurement Methods in Sandston Rocks - Aljawad, Mohammed Saleh; Ali, Abdullah Abdulhasan; Abdulkhadim, Marwah Dhahir (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
This paper displays a survey about the laboratory routine core analysis study on ten sandstone core samples taken from Zubair Reservoir/West Quarna Oil Field. The Petrophysical properties of rock as porosity, permeability, grain's size, roundness and sorting, type of mineral and volumes of shales inside the samples were tested by many apparatus in the Petroleum Technology Department/ University of Technology such as OFITE BLP-530 Gas Porosimeter, PERG-200TM Gas Permeameter and liquid Permeameter, GeoSpec2 apparatus (NMR method), Scanning Electron Microscopy (SEM) and OFITE Spectral Gamma Ray Logger apparatus. By comparing all the results of porosity and permeability measured by these instruments, it is clear a significant variation in the values with the depth within same formation.  The porosity by gas, liquid and NMR are varied (15.4 - 35.9) %, (4.6 - 22.3) % and (2.4- 13.5) % respectively, While the permeability by gas, liquid and NMR were altered (0 - 512) md, (0-139.6) md and (1.577 x10-6 – 492) md respectively.